2022
DOI: 10.1042/bst20210883
|View full text |Cite
|
Sign up to set email alerts
|

Strength in numbers: effect of protein crowding on the shape of cell membranes

Abstract: Continuous reshaping of the plasma membrane into pleomorphic shapes is critical for a plethora of cellular functions. How the cell carries out this enigmatic control of membrane remodeling has remained an active research field for decades and several molecular and biophysical mechanisms have shown to be involved in overcoming the energy barrier associated with membrane bending. The reported mechanisms behind membrane bending have been largely concerned with structural protein features, however, in the last dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…We expected that the membrane interactions would be stronger for NS1 ZIKV‑UG than for NS1 ZIKV‑BR , leading to a major protein clustering for the African variant on the surface of an ER lipid bilayer compared to the Asian strain. It has been shown that membrane curvature-inducer proteins increase the membrane bending effect as the number of them increases. , As mentioned previously, this may have direct consequences on the formation of the replication complex or on subsequent stages of NS1 maturation. Thus, NS1 ZIKV‑UG should have a higher viral particle production rate compared to NS1 ZIKV‑BR , which could have an immediate effect on the virulence, infection, and viral pathogenesis (see Figure ).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…We expected that the membrane interactions would be stronger for NS1 ZIKV‑UG than for NS1 ZIKV‑BR , leading to a major protein clustering for the African variant on the surface of an ER lipid bilayer compared to the Asian strain. It has been shown that membrane curvature-inducer proteins increase the membrane bending effect as the number of them increases. , As mentioned previously, this may have direct consequences on the formation of the replication complex or on subsequent stages of NS1 maturation. Thus, NS1 ZIKV‑UG should have a higher viral particle production rate compared to NS1 ZIKV‑BR , which could have an immediate effect on the virulence, infection, and viral pathogenesis (see Figure ).…”
Section: Introductionmentioning
confidence: 79%
“…It has been shown that membrane curvature-inducer proteins increase the membrane bending effect as the number of them increases. 31,32 As mentioned previously, this may have direct consequences on the formation of the replication complex or on subsequent stages of NS1 maturation. Thus, NS1 ZIKV-UG should have a higher viral particle production rate compared to NS1 ZIKV-BR , which could have an immediate effect on the virulence, infection, and viral pathogenesis (see Figure 1).…”
Section: ■ Introductionmentioning
confidence: 88%
“…For example, adsorption of molecules that change the spontaneous curvature of the membrane due to asymmetric tension can result in spontaneous tubulation [13]. Protein-protein crowding is also a significant driver of membrane tubulation [14]. Osmotic pressure resulting in volume reduction, or a growth in * mohsen.sadeghi@fu-berlin.de membrane area can also lead to the formation of stable membrane tubules [15].…”
Section: Introductionmentioning
confidence: 99%
“…14,15 The idea of lipids being responsible for clustering virus proteins at the cell surface is appealing, and indeed colocalization, and resulting crowding, of viral envelope proteins with massive ectodomain heads could produce an asymmetric lateral pressure across the membrane capable of driving bending and thus contribute to viral budding. 16,17 Eukaryotic cell membranes have been proposed to form dynamic lipid raft structures enriched with proteins, allowing the cells to perform lateral organization of proteins into nanoscale domains. 18 The presence of rafts, initially verified using disputed detergent resistant methods, has been suggested as the driving mechanism for recruitment of viral proteins to the budding site.…”
mentioning
confidence: 99%
“…For influenza viruses, clustering of hemagglutinin (HA) and neuraminidase (NA) in the plasma membrane is crucial for the assembly and budding of progeny virions. The mechanism behind the lateral organization of proteins in the plasma membrane remains enigmatic, but the plasma membrane lipids have been proposed to be responsible for recruitment of transmembrane proteins to nanoscale budding sites of virus infected cells. , The idea of lipids being responsible for clustering virus proteins at the cell surface is appealing, and indeed colocalization, and resulting crowding, of viral envelope proteins with massive ectodomain heads could produce an asymmetric lateral pressure across the membrane capable of driving bending and thus contribute to viral budding. , Eukaryotic cell membranes have been proposed to form dynamic lipid raft structures enriched with proteins, allowing the cells to perform lateral organization of proteins into nanoscale domains . The presence of rafts, initially verified using disputed detergent resistant methods, has been suggested as the driving mechanism for recruitment of viral proteins to the budding site .…”
mentioning
confidence: 99%